Systematic Review on Addiction to Social Networks in Adolescents between 2020-2022 - Colonio Caro, Julio Daniel (2023)
The COVID-19 pandemic showed the current relevance of the use of online communication technologies, including social networks, for daily life. However, this growing advance of virtual media can lead to problematic behaviors similar to those of addiction; mainly in adolescents, who are frequent users of the networks. The present study sought to analyze the manifestation of addiction to social networks in this population, within the Latin American area, for which a systematic review of studies carried out in the period from 2020 to 2022 was carried out. 230 references from specialized databases were obtained, which were analyzed following the PRISMA model standards and according to eligibility criteria, based on the PICO strategy. A total of 10 studies, with a total sample of 22,791 participants, mostly women, were included for the development of the review, being classified as high quality. Regarding the results, medium and high levels of addiction to social networks were evidenced in more than half of the adolescents evaluated. This review synthesizes the main findings and conclusions obtained from research carried out in Latin American countries, contributing to the knowledge of the patterns of dysfunctional use of virtual platforms by the adolescent population and considering the probable negative effects on mental health as a result of the social isolation measures adopted by the pandemic.